Industry competition and firm conduct: Joint determinants of risk–return relations. (6th July 2020) - Christensen, Michael; Knudsen, Thorbjørn; Nash, Ulrik W.; Stieglitz, Nils
Abstract: Research Summary: In this study, we offer a novel approach, establishing how firm conduct and competitive interactions among firms jointly provide microfoundations of risk–return relations. Firms influence each other, and the way they reciprocate these influences to cause mutual adjustments is a core feature of industry dynamics. This core feature fundamentally influences risk–return relations. Based on our approach, we develop models that allow us to trace how, at the microlevel, firm conduct in conjunction with competitive interactions generate risk–return relations, and how these are associated with macrolevel measures of industry concentration. That translates into an approach that affords fine‐grained predictions of risk–return relations based on the nature of competition in an industry—for example, Cournot or Bertrand—and observations of the industry's competitive intensity and concentration. Managerial Summary: The risk‐return trade‐off is of critical importance for strategic management. Yet, the relation between industry conditions and the shape of risk‐return relations is often unclear. We develop a framework that allows managers to understand how industry conditions generate risk‐return relations, and how these can be inferred from macro‐level measures of industry concentration. At the micro‐level, we show that low variation in operational implementation of strategies may, under some conditions, be associated with high variation as well as high means in financial returns. Our primary insight is that the risk‐return trade‐off changes with competitive intensity: Starting from industries with two or three firms, we show that increasing competitive intensity – higher number of firms, higher entry and exit barriers – gives rise to a predictable sequence of risk‐return relations that change over the life‐cycle of industries. Overall, we contribute a framework that allows managers to infer the risk‐return trade‐off for the industry that their business units are located in.